‫أدوات ‬‫التحليل‬ ‫المحاس‫بي ‬‫و‬ ‫إستخداماتها‬ ‫في‬ ‫ترشيد‬ ‫قرارات‬ ‫التسعير‬ ‫في ‬‫المؤسسة‬ ‫الإقتصادية‬ ‫"‬‫دراسة‬‫عينة‬ ‫من‬ ‫المؤسسات‬ ‫الإقتصادية‬ ‫بولايتي‬ ‫عنابة‬ ‫و‬ ‫سوق‬ ‫أهراس‬ ‫"‬ - ‫رشيدة‬ ‫لعبني‬ (My University, 2019)
The research work aimed to study the concept of “Pricing decision” and its different objectives beside to the factors influenced in it. Moreover, it attempts to define the different accounting analysis styles used in pricing the products among the interior departments of the institution which are represented in: the styles of transfer prices, the methods used in pricing the products, and also knowing to what extent these styles contribute in rationalizing pricing decisions. A program of statistics analysis (SPSSV22) is used to test the assumptions, and to analyze the results obtained from the answers that were taken from 65 questionnaires distributed on four economic institutions. The study shows that pricing decisions has a great importance in the economic institutions; which they depend basically on the costs to determine the transfer prices, and on the makeup profits to determine the customers’ products prices. Through the aims of the study and their results, we ended up with the following recommendations: it is necessary to make an academic training to convoy all what is new in the field of accounting, and about the other styles of accounting analysis.